Análise proteômica de saliva de pacientes com lesões potencialmente malignas e carcinoma de células escamosas intraorais - Brizeno, Luiz André Cavalcante (2018)
Oral cancer is a serious public health problem in Brazil. The most common histological type of malignancy in the oral cavity (90 to 95% of cases) is squamous cell carcinoma (SCC) an invasive and aggressive epithelial neoplasia and low survival mainly due to late diagnosis. Eventually, lesions that precede the appearance of malignant neoplasias, called potentially malignant lesions (PML), may occur, being oral leukoplakia (OL) the most common. There is a growing interest in the analysis of saliva through proteomics since this is a noninvasive and rich source of information and can provide not only an early diagnosis, but also a prognosis and monitoring of the treatment. Salivary proteomic analysis can be hampered by the presence of high abundance proteins that mask or reduce the sensitivity of separation. Lectins have been widely used to remove high abundance glycoproteins that could potentially undermine proteome analysis. This study aimed to evaluate for the first time proteins present in saliva of patients with OL and oral SCC in Ceará State, when compared to a group control, through proteomic techniques (one and two-dimensional electrophoresis followed by mass spectrometry) and molecular biology (Western Blot). A chromatographic column immobilized with the lectin isolated from the red algae Bryothamnion triquetrum (BTL) was used to remove high abundance protein from saliva (mucin). In parallel bioinformatics methodologies were used (modelling and molecular docking) to the comprehension of oral SCC molecular pathogenesis. Saliva pools were collected from 5 patients from each group with a diagnosis of CCE and LO, confirmed by histopathological exams and the protein profile of the groups compared to each other. The present study demonstrated for the first time the increase in the levels of ZG16B in the saliva pool of patients with Oral SCC when compared to the pool of the OL and control groups, it was also verified the increase of cytokeratin 1 in the SCC pool. Through bioinformatics assays ZG16B is structurally similar to the Artin M lectin and binds strongly to complex glycans by the mannide moiety. The study may contribute to the discovery of potentials salivary biomarkers in SCC, which may assist in the development of diagnostic and prognostic tools, directly influencing the patients survival and reduction of public health expenses.